1959
DOI: 10.1002/app.1959.070010107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon black on thermal antioxidants for polyethylene

Abstract: About 3% by weight of carbon black adequately protects polyethylene against photo‐oxidation and, under accelerated test conditions, slightly inhibits thermal oxidation. As a rule small amounts of organic antioxidants are also added to the polymer for optimum protection. Now many of the common phenolic and amine additives have been found to function much less effectively in polyethylene containing carbon black than in clear polymer. Loss of effectiveness is attributed to adsorption and/or decomposition of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Standard test methods were used for both the thermoanalytical lO and oxygen-absorption studies. 11 The stabilities of the samples other than black were all obtained on the thermal analyzer described above. Two measurements were made:…”
Section: Test Methodsmentioning
confidence: 99%
“…Standard test methods were used for both the thermoanalytical lO and oxygen-absorption studies. 11 The stabilities of the samples other than black were all obtained on the thermal analyzer described above. Two measurements were made:…”
Section: Test Methodsmentioning
confidence: 99%
“…[23][24][25][26][27][28] Figure 9 shows the MFI and the OIT data of samples PE15-PE17 expressed as the black masterbatch content using Figure 6 The relationship between the ESCR and the OIT value of the samples PE1-PE5 from both the one-step and two-step extrusion methods. …”
Section: The Effect Of Different Types Of Antioxidants On the Oitmentioning
confidence: 99%
“…Surprisingly the carbon black‐filled compound was less stable both in air and in nitrogen. Usually one expects carbon black to have little or no effect on the thermo‐oxidative degradation of polyolefins . However, Hawkins et al showed that addition of carbon black can adversely affect the performance of phenolic antioxidants commonly added to stabilize polyethylene against thermo‐oxidative degradation.…”
Section: Resultsmentioning
confidence: 99%